IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT BY USING REALIA - Mery Meilza Indria Aritonang and Johan Sinulingga (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2012)
This study attempted to improve students’ achievement in vocabulary by using Realia. This study was conducted by using classroom action research. The subject of the research was class VII-1 at SMP.N.17 Medan which consisted of 38 students. The research was conducted in two cycles, cycle I consisted of three meetings and cycle II consisted of three meetings. The instrument for collecting quantitative data was a vocabulary test and the instruments for collecting qualitative data included diary notes, observation sheets, questionnaire sheets, and interview. Based on the vocabulary test, students’ score kept improving in every test and based on the diary notes, observation sheets, questionnaire sheets, and interview report, it was found that the teaching-learning process ran well. Students were active, enthusiastic, and interested in vocabulary. The result of the research showed that Realia significantly improved students’ achievement in vocabulary. Key Words: Vocabulary, Realia, Diary Notes, Observation, Questionnaire, Interview.